Monitoring the optical degradation of green light-emitting diodes on the basis of measured electrical characteristics. (June 2021) - Herzog, Alexander; Wagner, Max; Khanh, Tran Quoc
Abstract: The degradation behavior and lifetime of LEDs for field operation is currently predominantly estimated using LM-80 data in combination with TM-21 extrapolations. If the environmental conditions differ significantly from the laboratory conditions of the LM-80 tests, differences in in-situ degradation behavior and TM-21 predictions could occur. Independently of the previous described methods, the following publication evaluates the use of an electro-optical model in order to allow an estimation of the in-situ degradation dynamics. The correlation between optical degradation and forward voltage decrease is determined on the basis of degradation tests performed on green high-power LEDs. Depending on the forward current selected, the correlation can be described by a linear or logarithmic function and can be used to build an electro-optical model that takes the degradation behavior for different operating conditions into account. A final validation of the model shows that the degradation behavior of individual LEDs can be determined, while a comparison of the measured mean values of four test LEDs with the model predictions shows a maximum root-mean-square error (RMSE) of 0.012. Accordingly, the method offers the possibility of condition monitoring that can be transferred into a practical measurement circuit. Highlights: Significant degradation of green high-power LEDs Correlations between optical and electrical degradation Empirical electro-optical model for condition monitoring could be used.